Design And Develop An Autonomous UAV Airship For Indoor Surveillance And Monitoring Applications - Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri; Kamis, Zalina; Mohd Aras, Mohd Shahrieel; Mohd Ali, Nursabillilah; Wasbari, Faizil; Abu Bakar, Mohd Nor Fakurazy (Information Technology Department, Politeknik Negeri Padang, 2018)
This project is about to develop an airship based on small size remotely controlled by human. The airship is one of Unmanned Airship Vehicle (UAV) which is can be apply in advertising, VIP security inspection, traffic monitoring and management and so on. The main purpose of this project is to design and develop an autonomous UAV airship for indoor surveillance and monitoring applications. The image will be captured from wireless camera where it mounted at a bottom of gondola. To determine the centroid points of the object are implemented in three phase edge detector, canny operator and threshold. The object will be display on Graphical User Interface (GUI) in 2D coordinated. In this project the systems able to detect only one object at one time.